Teknik Pembiakan Ikan Platy Sunrise (Xiphophorus sp.) Skala Kecil - Kasprijo Kasprijo; Rudy Wijaya; Ronald Pratama Putra; Bahar Surendra; Peri Prayunidinila; Ratika Nur Arifah; Alfi Saputra; Shakty Amaylia Roesdy; Ghinaa Maryana Nabila; Ahmad Hazimul Zuhdi; Paramitha Sekar Amelia; Salsabila Nur Wulandari; Muh. Sulaiman Dadiono; Christin Debora Hutabarat (PT. Gyandharma Global Media, 2025)
Sunrise platy fish (Xiphophorus sp.) breeding is one of the platy fish cultivation activities that aims to increase and multiply sunrise platy fish, starting from spawning to becoming seeds. This practical activity aims to determine the technique of sunrise platy fish breeding with different treatments. The methods used in this study were experiments and active participation. The variables observed were parent parameters including parent age, and characteristics of mature gonad parents, parent morphology, hatching rate (HR), survival rate (SR), and water quality. The sunrise platy fish breeding activity consists of several stages, namely preparation of spawning containers with treatments P1: using Malang sand without aquatic plants, P2: using Malang sand and aquatic plants, P3: not using Malang sand and aquatic plants, then parent selection, spawning, larval transfer, larval maintenance, disease management, water quality management. The results of this study obtained the highest fertilization value in P1 with a total of 45 fish larvae and an SR value of 100%.